2023
DOI: 10.1088/1741-4326/acb27c
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study on the slippage of liquid lithium flow in tungsten nanochannels

Abstract: As the use of liquid lithium (Li) as the plasma facing material in a fusion device becomes widespread, more and more research work has been dedicated to the numerical simulations of Li flow based on the Navier-Stokes equations. However, the slip condition of Li on a solid surface hasn’t been fully understood. The most common and simplest boundary condition, which is no-slip, is just one of the allowable conditions ranging from pure slip to multi-layer locking. In this work, molecular dynamics simulations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Under these conditions, energy confinement does not drop significantly (<10%) when ELM suppression is achieved compared with the ELMy H-mode conditions, while the core plasma tungsten concentration is clearly reduced as shown in Figure 14. This is very different from previous observations using low n (n=1 and 2) RMPs in EAST with high q95 (≥ 5), in which the plasma stored energy was significantly reduced (>20%) [55,56].…”
Section: 1elm Control By Rmpscontrasting
confidence: 99%
“…Under these conditions, energy confinement does not drop significantly (<10%) when ELM suppression is achieved compared with the ELMy H-mode conditions, while the core plasma tungsten concentration is clearly reduced as shown in Figure 14. This is very different from previous observations using low n (n=1 and 2) RMPs in EAST with high q95 (≥ 5), in which the plasma stored energy was significantly reduced (>20%) [55,56].…”
Section: 1elm Control By Rmpscontrasting
confidence: 99%
“…71 Similarly, NEMD studies of Couette flow demonstrated a transition from Newtonian fluid behavior at low shear rates to non-Newtonian behavior at high shear rates. 72,73 In the current investigation, the shear viscosity of nanoconfined water was computed as follows: 71…”
Section: Resultsmentioning
confidence: 99%